Laboratory misdiagnosis of von Willebrand disease in post‐menarchal females: A multi‐center study. Issue 9 (20th June 2020) - Jaffray, Julie; Staber, Janice M.; Malvar, Jemily; Sidonio, Robert; Haley, Kristina M.; Stillings, Amy; Weyand, Angela; Hege, Kerry; Jain, Shilpa; Gupta, Sweta; Agnew, Caroline; Wheeler, Allison; et al.
Abstract: Increased awareness of von Willebrand Disease (VWD) has led to more frequent diagnostic laboratory testing, which insurers often dictate be performed at a facility with off‐site laboratory processing, instead of a coagulation facility with onsite processing. Off‐site processing is more prone to preanalytical variables causing falsely low levels of von Willebrand Factor (VWF) due to the additional transport required. Our aim was to determine the percentage of discordance between off‐site and onsite specimen processing for VWD in this multicenter, retrospective study. We enrolled females aged 12 to 50 years who had off‐site specimen processing for VWF assays, and repeat testing performed at a consulting institution with onsite coagulation phlebotomy and processing. A total of 263 females from 17 institutions were included in the analysis. There were 251 subjects with both off‐site and onsite VWF antigen (VWF:Ag) processing with 96 (38%) being low off‐site and 56 (22%) low onsite; 223 subjects had VWF ristocetin co‐factor (VWF:RCo), 122 (55%) were low off‐site and 71 (32%) were low onsite. Similarly, 229 subjects had a Factor VIII (FVIII) assay, and 67 (29%) were low off‐site with less than half, 29 (13%) confirmed low with onsite processing. Higher proportions of patients demonstrated low VWF:Ag, VWF:RCo, and/or FVIII with off‐site processing compared to onsite (McNemarʼs test P ‐value <.0005, for all assays). These results emphasize the need to decrease delays from sample procurement to processing for VWF assays. The VWF assays should ideally be collected and processed at the same site under the guidance of a hematologist.